2019
DOI: 10.7150/jca.30816
|View full text |Cite
|
Sign up to set email alerts
|

An NF90/long noncoding RNA-LET/miR-548k feedback amplification loop controls esophageal squamous cell carcinoma progression

Abstract: In our previous study we have found that miR-548k has oncogenic roles in esophageal squamous cell carcinoma (ESCC) via repressing long noncoding RNA (lncRNA)-LET and further upregulating nuclear factor 90 (NF90). However, the upstream factors controlling miR-548k expression are still unknown. In this study, we found NF90 directly binds pri-miR-548k, increases the stability of pri-miR-548k, and upregulates the expression of pri-miR-548k and miR-548k. Therefore, NF90, miR-548k and lncRNA-LET forms a feedback loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Several feedback loops have been reported to be employed by cancer cells to exert their malignant behaviors, such as ERIC/E2F, miR-200a/HDAC4, SNHG14/ miR-5590-3p/ZEB1, NF90/lncRNA-LET/miR-548k, and so on. [52][53][54][55] Functional rescue experiments showed that inhibition of ERK activation or silencing of PCDH7 abrogated the oncogenic roles of LNAPPCC in colon cancer, which suggested that the LNAPPCC/ PCDH7/ERK/c-FOS feedback loop at least partially mediates the oncogenic roles of LNAPPCC in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several feedback loops have been reported to be employed by cancer cells to exert their malignant behaviors, such as ERIC/E2F, miR-200a/HDAC4, SNHG14/ miR-5590-3p/ZEB1, NF90/lncRNA-LET/miR-548k, and so on. [52][53][54][55] Functional rescue experiments showed that inhibition of ERK activation or silencing of PCDH7 abrogated the oncogenic roles of LNAPPCC in colon cancer, which suggested that the LNAPPCC/ PCDH7/ERK/c-FOS feedback loop at least partially mediates the oncogenic roles of LNAPPCC in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, NF90 has been found to be differentially expressed in several types of cancers such as ovarian, breast, cervical, hepatocellular and nasopharyngeal carcinomas, leukemia, and bladder cancer [ 22 , 37 , 42 , 43 , 44 ]. While the impact of NF90 on cancer proliferation, progression, metastasis, and drug resistance is evident, its role in these processes is divergent and may depend on the cancer type.…”
Section: Functions Of Nf90mentioning
confidence: 99%
“…On the other hand, NF90 can also bind and stabilize oncogenic pri-miRNAs such as pri-miR-548k, which is implicated in esophageal squamous cell carcinoma (ESCC), promoting cancer progression, metastasis, and poor overall survival [ 42 , 57 ]. Interestingly, miR-548k was shown to upregulate NF90 and downregulate lncRNA-LET, which acts as a tumor suppressor, establishing a feedback amplification loop that controls ESCC progression and metastasis [ 42 , 57 ].…”
Section: Functions Of Nf90mentioning
confidence: 99%
“…In another instance, the suppressors of cytokine signaling (SOCS-1 and SOCS-3) were revealed to be implicated in ESCC progression ( 19 ). Moreover, the association of lncRNA TUSC7, miR-616, and SOCS4 has been revealed in endometrial carcinoma ( 16 , 20 ). Notably, miR-1290 was abnormal in lung adenocarcinoma, contributing to cancer progression through targeting SOCS4 ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, lncRNAs serve as the spongers of microRNAs (miRNAs) that are abnormally expressed in various tumors ( 13 , 14 ), affecting other target genes via base pairing ( 15 ),—for instance, it was reported that the miR-548k in ESCC exerted oncogenic functions through downregulating the lncRNA-LET expression ( 16 ). On the contrary, upregulation of miR-93-5p and miR-106b-5p within esophageal carcinoma has been reported in the literature ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%